2012
DOI: 10.4103/0970-9371.103942
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of modified ultrafast Papanicolaou stain with the standard rapid Papanicolaou stain in cytology of various organs

Abstract: Background:Since the first introduction of Papanicolaou (Pap) stain in 1942 there have been many modifications. Of these, the Ultra-Fast Pap stain has become popular. This technique was further modified in India as many of the reagents were not available in our country. Our study was conducted by adapting this modified staining technique which involves the replacement of Gill's hematoxylin with Harris hematoxylin.Aims:The aim of our prospective study was to assess the use of the modified Ultra-Fast Pap stain (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 7 publications
1
27
0
Order By: Relevance
“…Again, SAP agrees with MEM (45% reduction in consumables), which has been published by Odigie and Obaseki [1] ; and is also consistent with the report by Gupta et al [3] , which favors minimum alcohol use but disagrees with Dighe et al [2] ; where 25% reduction was achieved. In respect to the turn-around time, SAP (5±0.5) partially aligns with MEM (7±0.5) by Odigie and Obaseki [1] and the report by Choudhary et al [4] but is dissimilar to RAT as reported by Richard [5] . In an earlier report, SAP staining quality agrees with MEM, which was well preserved even after some months of storage and is essential for smear review and retrospective studies [1,8,13,14] .…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Again, SAP agrees with MEM (45% reduction in consumables), which has been published by Odigie and Obaseki [1] ; and is also consistent with the report by Gupta et al [3] , which favors minimum alcohol use but disagrees with Dighe et al [2] ; where 25% reduction was achieved. In respect to the turn-around time, SAP (5±0.5) partially aligns with MEM (7±0.5) by Odigie and Obaseki [1] and the report by Choudhary et al [4] but is dissimilar to RAT as reported by Richard [5] . In an earlier report, SAP staining quality agrees with MEM, which was well preserved even after some months of storage and is essential for smear review and retrospective studies [1,8,13,14] .…”
Section: Discussionsupporting
confidence: 61%
“…Papanicolaou staining has been in use for decades and has been published to date [1,[3][4][5][6][7][8][9][10] . This study was a follow-up to an existing work and an adaptation of the study by Odigie and Obaseki [1] .…”
Section: Staining Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…[12] To overcome these problems, Yang and Alvarez developed UFP stain which is a hybrid of Romanowsky and conventional PAP stain to reduce the staining time to 90 s.[1] Kamal et al . modified the UFP to overcome the problems of shortage of Richard-Allan Hematoxylin, Richard-Allan cytostain, and ethyl alcohol reagents in Indian set up.…”
Section: Discussionmentioning
confidence: 99%